Production of HSVd- and PPV-free apricot cultivars by in vitro thermotherapy followed by meristem culture - C. Pérez-Caselles; L. Burgos; E. Yelo; L. Faize; N. Alburquerque (Plant Methods, 2025)
Abstract Background The production of virus-free apricots (Prunus armeniaca L.) is essential for controlling viral diseases, exchanging breeding materials without the risk of spreading new diseases, and preserving plant germplasm. Plum pox virus (PPV) is the most devastating disease of the Prunus genus and Hop stunt viroid (HSVd) is prevalent in most apricot-growing regions. It was evaluated whether thermotherapy, etiolation, or a combination of both followed by meristem culture could effectively eliminate PPV and HSVd from ‘Canino’ and ‘Mirlo Rojo’ apricot cultivars in vitro. Results In the thermotherapy treatments, shoots were exposed to 38ºC and 32ºC, alternating every four hours, for 30, 35, 40, and 45 days. Before this, shoots were acclimated to heat for one day at 28ºC and two days at 30ºC. Etiolation experiments consisted of eight weeks of culture in dark conditions. A combination of 45 days of thermotherapy, as described previously, and etiolation was also performed. At the end of each treatment, 1.5 mm meristems were cultured, and developed as potential independent pathogen-free lines. The presence or absence of pathogens was analysed by RT-PCR. The 45 days of thermotherapy and the combined thermotherapy and etiolation treatments resulted in the highest percentages of PPV-free plants (66.7 and 75.0%, respectively). At least 40 days of thermotherapy were required to obtain HSVd-free plants, although the best efficiency was achieved at 45 days (22.7%). Conclusions In this study, we have developed an effective in vitro thermotherapy protocol that eliminates PPV and HSVd from apricot cultivars. This is the first report where a thermotherapy protocol eliminates HSVd in Prunus species.